Policy Development of the Child-Friendly City: Case Study of South Tangerang City Regional Government - Satispi, Evi (International Journal of Social and Administrative Sciences, 2019)
This study aims to find out the Policy Development of the City of South Tangerang to implement the Ministerial Regulation of the Women's Empowerment and Child Protection of the Republic of Indonesia Number 11 of 2011, regarding the Child-Friendly City Development Policy using a qualitative approach and descriptive research methods. That is to explain phenomena in depth through data collection. This type of research provides an overview, an accurate explanation objectively about the actual state of the object under study. Research design uses the theory of public policy making according to Metter and Horn. The results of the South Tangerang development research generally went well. Among them; achievement of basic health and welfare, the large number of breastfeeding facilities and breastfeeding corners, high percentage of complete basic immunizations for children, low prevalence of malnutrition in children under five, low infant mortality rate (IMR), as well as active and outstanding ARHCIC (Adolescent Reproductive Health Counseling Information Center).